The Deletion of the MGF360-10L/505-7R Genes of African Swine Fever Virus Results in High Attenuation but No Protection Against Homologous Challenge in Pigs - Linlin Zheng; Zilong Yan; Xiaolan Qi; Jingjing Ren; Zhao Ma; Huanan Liu; Zhao Zhang; Dan Li; Jingjing Pei; Shuqi Xiao; Tao Feng; Xinglong Wang; et al. (Viruses)
African swine fever virus (ASFV) is the causative agent of African swine fever (ASF), a severe hemorrhagic disease with a mortality rate reaching 100%. Despite extensive research on ASFV mechanisms, no safe and effective vaccines or antiviral treatments have been developed. Live attenuated vaccines generated via gene deletion are considered to be highly promising. We developed a novel recombinant ASFV strain by deleting MGF360-10L and MGF505-7R, significantly reducing virulence in pigs. In the inoculation experiment, pigs were infected with 104 50% hemadsorption doses (HAD50) of the mutant strain. All the animals survived the observation period without showing ASF-related clinical signs. Importantly, no significant viral infections were detected in the cohabitating pigs. In the virus challenge experiment, all pigs succumbed after being challenged with the parent strain. RNA-seq analysis showed that the recombinant virus induced slightly higher expression of natural immune factors than the parent ASFV; however, this level was insufficient to provide immune protection. In conclusion, our study demonstrates that deleting MGF360-10L and MGF505-7R from ASFV CN/GS/2018 significantly reduces virulence but fails to provide protection against the parent strain.